Growth, nutritional profile and antioxidant properties of marine microalgae used as live feed for aquaculture organisms - Abdurahman, Norazira; Khatoon, Helena; Yusuf, Norhayati; Haris, Azilah; Banerjee, Sanjoy (Penerbit Universiti Malaysia Terengganu, 2016)
In aquaculture, microalgae are used to provide nutrition needed by the aquaculture organism which makes it a very important food source in aquaculture. Microalgae have also attracted increasing attention as animal feed supplement due to their bioactive constituent which contributed to their functional properties. Even under normal culture condition, growth, nutritional value and antioxidant properties of microalgae vary between species. A study was performed to determine the growth, nutritional profile and antioxidant properties of Nannochloropsis maculate, Chaetoceros calcitrans and Tetraselmis chuii. Tetraselmis chuii obtained higher cell density with a shorter growth phase compared to N. maculate and C. calcitrans. In addition, highest protein content was also found in T. chuii at 51.4%. On the other hand, N. maculate showed the highest lipid and carbohydrate content compared to the other two species. Meanwhile, the selection of microalgae with high antioxidant activity in three species of marine microalgae, T. chuii, N. maculate and C. calcitrans were carried out by a screening test using five antioxidant chemical assays (Antioxidant activity, scavenging effect on superoxide radical and DPPH radical, ferric reducing antioxidant potential (FRAP) and total phenolic content). Highest antioxidant activity, free radical scavenging activities and total phenolic content was found in T. chuii which makes it a highly potential species as feed additives for aquaculture organisms. Present findings could be considered when culturing the three microalgae species to provide appropriate levels of nutrition and antioxidant as feed supplement for aquaculture organisms.